Low impact fiber reinforced material composite - Juárez Alvarado, César Antonio; González López, Javier Rodrigo; Mendoza Rangel, José Manuel; Zaldivar Cadena, Antonio Alberto (Revista ALCONPAT, 2017)
This article investigates the mechanical behavior of fiber-reinforced cementitious composites using moderate to high contents of fly ash (FA) as a replacement for cement; the goal is to create primary building elements with low environmental impact. The experimental results showed that the compressive strength, modulus of elasticity, and post-cracking flexural strength for specimens with w/cm = 0.60 and 20% FA substitution increased with respect to the control. Moreover, the specimens with high FA substitutions had significantly lower mechanical strength values and elastic modulus values. The results indicate that it is feasible to use fiber-reinforced concrete composites as an alternative for low-environmental impact primary construction.